Impact of End User Development Technical and Environmental Factors on Software Cost - Srivastava, Archana; S KSingh, Dr.; Syed Qamar Abbas, Dr. (International Journal of Engineering and Technology, 2018)
Software project manager is confronted with the dilemma of accurate estimation at the very beginning of the project. Quantitative estimates are required at the early stages of development. Software cost estimation is accounted as an important factor while making estimations in Software Engineering. There is no simple way to make an accurate estimate of the effort required to develop software systems incorporating EUD/EUP because of many reasons like unclear user requirements, lack of knowledge on new technology, changing technology requirements and unavailability of solid information. End users were significantly more satisfied with applications they had developed themselves and which possess quality parameters as per their requirements. If the software incorporates End user development features then additional effort may be required in development and designing the EUD features. This paper discusses the impact of end user quality parameters on the overall effort of the software development. It includes a comparative analysis of UCP with my published model AUCP in terms of effort. It also ponders cases where End user development should be positively considered as an additional cost driver for effort estimation.Â Â
Keywords: Use Case Point Method (UCP); Advance Use Case Point Method (AUCP); End User Development (EUD); Human Computer Interaction (HCI); End User Computing (EUC); Technical Complexity Factors (TCF); Environmental Complexity Factors (ECF).